2013
DOI: 10.1186/1423-0127-20-85
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala opioid receptors mediate the electroacupuncture-induced deterioration of sleep disruptions in epilepsy rats

Abstract: BackgroundClinical and experimental evidence demonstrates that sleep and epilepsy reciprocally affect each other. Previous studies indicated that epilepsy alters sleep homeostasis; in contrast, sleep disturbance deteriorates epilepsy. If a therapy possesses both epilepsy suppression and sleep improvement, it would be the priority choice for seizure control. Effects of acupuncture of Feng-Chi (GB20) acupoints on epilepsy suppression and insomnia treatment have been documented in the ancient Chinese literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…4h ). These data are adapted from our previous observations in order to reduce the use of animals [ 22 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…4h ). These data are adapted from our previous observations in order to reduce the use of animals [ 22 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…4a ), except for sleep suppression of NREM and REM sleep during the first 4 h of the dark period. Our previous results have demonstrated that the anesthetization of rats for 30 min with ketamine, an NMDA receptor antagonist, prior to the dark period suppressed both NREM sleep and REM sleep during the first four hours of the dark period [ 12 , 22 ]. Therefore, the decreases of NREM sleep and REM sleep during the first 4 h of the dark period when rats received the 10 Hz sham EA stimuli and were under anesthetization were primarily due to the effect of tiletamine, a composition of zoletil.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations